Investigation on Mother's Activities in Assisting Kindergarten Students in Online Learning - Tarmilia Tarmilia; Wahyu Hanan Hapsari; Sri Lestari (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The change from face-to-face learning to an online learning method during a pandemic requires parents to adapt. Kindergarten students who originally studied at school are now learning more at home and parents should be more involved. Therefore, this study aims to investigate the activities of mothers while accompanying children to learn online. Research informants are two mothers who have kindergarten students. Qualitative data were obtained through interviews and observations as long as mothers accompanied students in online learning. The data obtained were analyzed by descriptive analysis techniques. We found that mothers did not start and end their learning by inviting their children to pray, tended to criticize their children's work, dictate what to write and do on pictures, and erase their children's writings. On the other hand, there are mothers who give freedom to their children, even while doing other activities. Mother gave less appreciation and was in a hurry because she had to continue with work. Meanwhile, a mother needs to get self-motivated support, obedient child character, husband and family involvement, and teacher involvement. There are mothers who are visited by teachers, but some are not. Mothers encounter obstacles due to economic limitations which result in a lack of learning facilities and limited time, there are mothers who are tired because they must work, there are fathers who are involved and some are less involved, and parents do not communicate with teachers. This shows that there has not been a good partnership between parents and teachers. Fathers are expected to be more involved in assisting children in learning. Cooperation between mothers and fathers should be increased so that children can study comfortably.